Effect of the surfactant benzalkonium chloride in the sorption of paraquat and cadmium on montmorillonite - Ilari, Romina (2014)
Pesticides, heavy metals and surfactants can share the same region or site in the environment and thus they may compete for the surface of minerals. A competitive study of the adsorption between the cationic surfactant benzalkonium chloride (BAC) with the heavy metal cadmium (Cd(II)) and the cationic herbicide paraquat (PQ) on montmorillonite is presented. Adsorption isotherms for BAC, PQ and Cd(II) were performed in single solute systems and also in binary solute systems, PQ+BAC and Cd(II)+BAC to evaluate the effects of BAC on the adsorption of the other two substances. The affinities of BAC and PQ were strong and similar, thus BAC affected significantly the adsorption of PQ and vice versa. The affinity of Cd(II) for the montmorillonite surface was low, thus BAC affected appreciably Cd(II) adsorption, but the heavy metal did not modify BAC adsorption. XRD data show that BAC molecules control the magnitude of the basal spacing.